The Problem of Transforming Synagogues into Christian Churches and Christian churches into Synagogues: Archaeological Evidence - Tarkhanova, Svetlana V. (Actual Problems of Theory and History of Art, 2015)
The problem of transforming synagogues into Christian churches and vice versa is parallel and synchronous to the problem of transforming Pagan temples, but the investigation of the former is far from completion. In this article I propose a brief review of all archaeologically known cases of church-synagogue rebuilding in the territory of the Late Antique Palestine (Gerasa, Hippos-Sussita, Sumaqa, Nazareth, etc.). From a large and not too systematic number of historical references concerning conflicts between Christians and Jews only some of them relate to archaeological data (Apamea). Several churches and synagogues adjacent to each other within a polis space, even when architectural plans are nearly similar, still make some peculiarities of self-identification obvious even during peaceful periods (Tiberias, Sepphoris, Beith She’an, and Capernaum). Special attention is paid to the Gaza “synagogue” and its initial genesis. A supposition exists that it was built as a church in the 5th–6th centuries, but in the year 638 (Arabian invasion) the basilica passed into the hands of Jews, and was rebuilt into Beit Knesset. Chronology of confessional rebuilding shows irreversible development of relations between Jews and Christians through centuries.
Keywords: Palestine; Late Antiquity; synagogues; Christian churches; reconstruction of synagogues and churches; archaeology; confessional antagonism; architectural self-identification of Judaism and Christianity